2005
DOI: 10.1111/j.1365-2044.2005.04137.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from percutaneous dilatational tracheostomy. A report of three cases*

Abstract: SummaryWe report three deaths following percutaneous dilatational tracheostomy in a series of 1187 procedures undertaken in a single intensive care unit over a 13‐year period. All deaths were due to severe haemorrhage. The first patient died during the procedure from uncontrollable haemorrhage from the innominate vein. Delayed haemorrhage in the other two patients was caused by the tracheostomy tube eroding into the aorta in one patient and into the innominate vein in the other. In both these patients, the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 21 publications
0
52
0
1
Order By: Relevance
“…aberrant arterial anatomy have been reported [15,16]. Likewise, the small incision reduces bacterial colonisation and infection of the stoma.…”
Section: No Patientsmentioning
confidence: 99%
“…aberrant arterial anatomy have been reported [15,16]. Likewise, the small incision reduces bacterial colonisation and infection of the stoma.…”
Section: No Patientsmentioning
confidence: 99%
“…Krwotoki będące powikłaniem PTD można podzielić na występujące w trakcie zabiegu, będące skutkiem bezpośredniego uszkodzenia naczynia w polu operacyjnym oraz późniejsze spowodowane najczęściej powstaniem przetoki tchawiczo-tętni-czej [6,7]. Pojawienie się nieprawidłowego połą-czenia najczęściej związane jest z wytworzeniem się martwicy ściany tchawicy, powstałej, np.…”
unclassified
“…Haemorrhages representing complications of PDT can be divided into two types: intraoperative haemorrhages resulting from direct blood vessel injury in the operative field, and delayed haemorrhages caused primarily by the development of a tracheoarterial fistula [6,7]. The formation of an abnormal connection is usually associated with necrosis in the tracheal wall which can arise, for example, from excessively high cuff pressure in the intubation or tracheotomy tube [6].…”
mentioning
confidence: 99%
“…3 Fatal haemorrhage from PT is a known but rare complication, although it is thought to be under-reported. 4 One study highlighted injury to blood vessels, which could have possibly been identified using ultrasound. 5 It was considered significant in 24 (5%) of 497 PT procedures performed without ultrasound evaluation prior to tracheal dilatation.…”
Section: Introductionmentioning
confidence: 99%